Loss of the ubiquitin conjugating enzyme UBE2E3 induces cellular senescence - Plafker, Kendra S. (Redox Biol, 2018)
Cellular senescence plays essential roles in tissue homeostasis as well as a host of diseases ranging from cancers to age-related neurodegeneration. Various molecular pathways can induce senescence and these different pathways dictate the phenotypic and metabolic changes that accompany the transition to, and maintenance of, the senescence state. Here, we describe a novel senescence phenotype induced by depletion of UBE2E3, a highly-conserved, metazoan ubiquitin conjugating enzyme. Cells depleted of UBE2E3 become senescent in the absence of overt DNA damage and have a distinct senescence-associated secretory phenotype, increased mitochondrial and lysosomal mass, an increased sensitivity to mitochondrial and lysosomal poisons, and an increased basal autophagic flux. This senescence phenotype can be partially suppressed by co-depletion of either p53 or its cognate target gene, p21(CIP1/WAF1), or by co-depleting the tumor suppressor p16(INK4a). Together, these data describe a direct link of a ubiquitin conjugating enzyme to cellular senescence and further underscore the consequences of disrupting the integration between the ubiquitin proteolysis system and the autophagy machinery.